Plasma-induced trilayer separator for lithium-ion batteries - Chong, Zhen Kang (Nanyang Technological University, 2021)
The separator is a crucial component in the lithium-ion batteries (LIBs) system as it will affect the battery performance. Yet, commercial battery separators such as polypropylene (PP) and polyethylene (PE) have low surface energy hydrophobic surfaces which results in low wettability and inability to absorb or retain the electrolyte. This will inhibit the overall electrochemical battery performance. Therefore, there is a need to alter the surface properties to fulfil the requirements of the current and future high-performance batteries.